The Fragments of Canticles from Qumran: Implications and Limitations for Interpretations - Gault, Brian P. ca. 20./21. Jh. (Revue de Qumran, 2010)
This article reviews the textual evidence for Canticles at Qumran, specifically examining the two 'abbreviated' manuscripts (4QCanta,b) which omit segments of the canonical text. While these omissions are clearly evident, the reason for such abbreviation is anything but clear. Various motivations have been suggested to explain this phenomenon, yet many of these theories conflict with evidence in the Song or the non-biblical scrolls. While these manuscripts likely served a purpose other than transmitting Scripture, the present lack of internal and external evidence prevents further conclusions regarding the function of these fragments. Thus, scholars should avoid using 4QCanta,b as support for speculation on the use of similar fragments or the interpretation of Canticles at Qumran. Numerous questions are put forward in an attempt to advance research on the use of these fragments.\n4207 \n4207